Unraveling the organellar genomic landscape of the therapeutic and entheogenic plant Mimosa tenuiflora: insights into genetic, structural, and evolutionary dynamics - Trinca, Vitor [UNESP]; Silva, Saura R. [UNESP]; Almeida, João V. A. [UNESP]; Miranda, Vitor F. O. [UNESP]; Costa-Macedo, José V.; Carnaval, Tatiane K. B. A.; Araújo, Draulio B.; Prosdocimi, Francisco; Varani, Alessandro M. [UNESP] (Springer Nature, 2025)
Mimosa tenuiflora, popularly known as “Jurema-Preta”, is a perennial tree or shrub native to the tropical regions of the Americas, particularly among Afro-Brazilian and Indigenous Brazilian communities. Known for producing N,N-Dimethyltryptamine, a psychedelic compound with profound psychological effects, Jurema-Preta has been studied for its therapeutic potential in mental health. This study offers a comprehensive analysis of the plastid (ptDNA) and mitochondrion (mtDNA) genomes of M. tenuiflora. The 165,639 bp ptDNA sequence features the classical quadripartite structure with 130 protein-coding genes. Comparative genomics among Mimosa species shows high sequence identity in protein-coding genes, with variation in the rpoC1, clpP, ndhA, and ycf1 genes. The ptDNA junctions display distinct features, such as the deletion of the rpl22 gene, and specific simple sequence repeats highlight genetic variation and unique motifs as valuable genetic markers for population studies. Phylogenetic analysis places M. tenuiflora in the Caesalpinioideae, closely related to M. pigra and M. pudica. The 617,839 bp mtDNA sequence exhibits a complex structure with multiple genomic arrangements due to large repeats, encoding 107 protein-coding genes, including the ptDNA petG and psaA genes, and non-retroviral RNA mitoviruses sequences. Comparative analysis across Fabaceae species reveals limited conservation, emphasizing the dynamic nature of plant mitochondrial genomes. The genomic characterization of M. tenuiflora enhances understanding of its evolutionary dynamics, providing insights for population studies and potential applications in ethnopharmacology and conservation.
Keywords: Alternative mtDNA arrangements; Comparative genomics; DMT; Ethnobotany; Fabaceae phylogeny